2008
DOI: 10.1149/1.2912040
|View full text |Cite
|
Sign up to set email alerts
|

PVA-PSSA Membrane with Interpenetrating Networks and its Methanol Crossover Mitigating Effect in DMFCs

Abstract: A membrane with interpenetrating networks between poly͑vinyl alcohol͒ ͑PVA͒ and poly͑styrene sulfonic acid͒ ͑PSSA͒ coupled with a high proton conductivity is realized and evaluated as a proton exchange membrane electrolyte for a direct methanol fuel cell ͑DMFC͒. Its reduced methanol permeability and improved performance in DMFCs suggest the new blend as an alternative membrane to Nafion membranes. The membrane has been characterized by powder X-ray diffraction, scanning electron microscopy, time-modulated diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
5
63
0
Order By: Relevance
“…It was found that the proton conductivity of the PVA/PSSA or PVA/PSSA-PMA semi-IPN membranes was strongly dependent on the content of the linear acid polymer. Maximum proton conductivity (~10 Semi-IPNs combining linear PSSA and PVA-GA polymer networks, showing high proton conductivities and high water retention capabilities for PEM applications in fuel cells, have also been prepared [60,68]. The maximum proton conductivity was observed for a PVA/PSSA semi-IPN membrane with about 35 wt% PSSA (PVA/PSSA 35 wt%) at all humidity values (0-100% RH).…”
Section: Pva Polymer Network Based Semi-ipn Membranesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the proton conductivity of the PVA/PSSA or PVA/PSSA-PMA semi-IPN membranes was strongly dependent on the content of the linear acid polymer. Maximum proton conductivity (~10 Semi-IPNs combining linear PSSA and PVA-GA polymer networks, showing high proton conductivities and high water retention capabilities for PEM applications in fuel cells, have also been prepared [60,68]. The maximum proton conductivity was observed for a PVA/PSSA semi-IPN membrane with about 35 wt% PSSA (PVA/PSSA 35 wt%) at all humidity values (0-100% RH).…”
Section: Pva Polymer Network Based Semi-ipn Membranesmentioning
confidence: 99%
“…However, the excessive swelling of PVA-PWA composite membranes limits their mechanical strength. For PEM applications, PVA is commonly incorporated into the PEM as a crosslinked partner via aldol condensation [60][61][62][63][64][65][66][67][68][69][70] or esterification [49,[71][72][73][74][75][76] to form a 3D network structure. Moreover, the degree of crosslinking of the PVA-based membranes has been shown to be easy to control via successive chemical treatments (aldol condensation or esterification).…”
Section: Poly (Vinyl Alcohol) (Pva)mentioning
confidence: 99%
See 3 more Smart Citations